2022
DOI: 10.1108/bfj-01-2022-0018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of social media addiction on eating behavior, body weight and life satisfaction during pandemic period

Abstract: PurposeThe aim of this study was to evaluate the relationship between social media addiction and eating behavior, eating disorder risk, body weight and life satisfaction in university students during pandemic period.Design/methodology/approachThe sample consists of 1,411 university students. Data were collected using online questionnaire and Scale of Social Media Usage Motives, Social Media Addiction Scale-Student Form, Dutch Eating Behavior Questionnaire (DEBQ), SCOFF Eating Disorders Scale and Life Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
(106 reference statements)
1
7
0
2
Order By: Relevance
“…Al Saud et al [26] also demonstrated a positive relationship between social network addiction and body mass index in Saudi Arabian university students. Ayyıldız and Şahin [27] have also shown a positive relationship between both variables in university students during the COVID-19 pandemic period.…”
Section: Introductionmentioning
confidence: 91%
“…Al Saud et al [26] also demonstrated a positive relationship between social network addiction and body mass index in Saudi Arabian university students. Ayyıldız and Şahin [27] have also shown a positive relationship between both variables in university students during the COVID-19 pandemic period.…”
Section: Introductionmentioning
confidence: 91%
“…Marketing strategies on these platforms often integrate with engaging and entertaining content, encouraging individuals to share these experiences with peers (Coates et al, 2019). However, the impact of social media and advertisements on the risk of developing adverse physical and mental health outcomes, including food allergies and overall well-being, may vary depending on the nutritional value of the products being promoted (Ayyıldız & Şahin, 2022).…”
Section: Societal Factors Have An Influence On Food Choice Behaviour ...mentioning
confidence: 99%
“…We chose to include these two sections because the first is critical for the analysis, as it explores the research gaps examined in this study, while the second is particularly valuable because it both enriches our database and provides a deeper understanding of who our respondents are based on personal aspects such as gender, age, and place of residence. To make the questionnaire easier for participants to answer, and in line with previous research (Ayyıldız and S ¸ahin, 2022), a Likert-type scale ranging from 1 (strongly disagree) to 7 (strongly agree) was used. The survey questions were tested by two academic experts with experience in customization research.…”
Section: Survey Instrumentmentioning
confidence: 99%